An analysis of synthetic absorbable sutures using solid-state NMR and DSC - Desai, Dr. Anish; Ajithkumar, Dr. T. G.; Bhat, Dr. Suresh (Journal of Medical Biomedical and Applied Sciences, 2019)
Sutures have become an essential part of the medical device/surgical industry. Polymers have played an important role in the development of synthetic sutures. Among all synthetic absorbable suture materials, Polyglactin 910 is one of the best polymer in terms of its biocompatibility, quick absorption, better tensile strength, controlled biodegradation. Two different absorbable surgical sutures such as MITSU AB™ and VICRYL® PLUS were analyzed using 13C cross-polarization magic angle sample spinning (CPMAS) technique and differential scanning calorimetry (DSC) to study their chemical composition and physicochemical properties respectively. When 2 spectra of MITSU AB™ and VICRYL® PLUS were compared, VICRYL® PLUS samples showed the peaks from glycolide and lactide while MITSU AB™ sample showed peaks due to glycolide group. When MITSU AB™ and VICRYL® PLUS were analyzed by DSC, melting temperature (Tm) for MITSU AB™ was not in the range with that of Polyglactin 910. When 13C nuclear magnetic resonance (NMR) spectrum of MITSU AB™ and VICRYL® PLUS were compared, it indicated that MITSU AB™ lacked the lactide group which was an essential part of Polyglactin 910 copolymer. Signature profile of MITSU AB™ was compared with that of VICRYL® PLUS profile and it was found that MITSU AB™ is different than that of VICRYL® PLUS signature profile and can be inferred to be a new or different polymer but not polyglactin 910.